Membumikan Tradisi Gotong Royong Dikalangan Mahasiswa Ma'had Aly Sunan Ampel UIN Malang - Mumtaz A., M. Labib; Sajieda, Layyina; Nur Abdillah, Muhammad Thaif; Layli, Hayyina Zulfatul (JPNM Jurnal Pustaka Nusantara Multidisiplin, 2025)
This study aims to explore the role of mutual cooperation in student life, particularly in the context of academic and social activities within higher education institutions. Using a qualitative approach with a case study method, data were collected through in-depth interviews, participatory observation, and documentation involving students from various academic programs. The findings reveal that mutual cooperation plays a significant role in fostering solidarity, enhancing the effectiveness of group work, and strengthening social responsibility among students. The values of togetherness, care, and mutual assistance serve as a foundation that strengthens relationships among students and supports the creation of a conducive academic atmosphere. The study concludes that the spirit of mutual cooperation should be continuously promoted in student activities as part of character building and the development of integrity among the younger generation.